The Effect of Reward Implementation and Non-Financial Work Environment on Employee Loyalty at Toko Femina Metro Lampung - Hikmatul Aliyah; Buchori Buchori; Sugiono Sugiono; Dame Dwinta Sari (Journal of Research in Social Science and Humanities, 2026)
This study aims to analyze the effect of reward implementation and work environment on employee loyalty at Toko Femina Metro. The research employs a quantitative approach with a survey method. The population and sample consist of 35 employees, selected using a saturated sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression analysis with SPSS.The results show that rewards have a positive and significant effect on employee loyalty. Likewise, the work environment also has a positive and significant effect on employee loyalty. Simultaneously, rewards and the work environment significantly influence employee loyalty, with a coefficient of determination (R²) of 0.536, indicating that 53.6% of employee loyalty can be explained by the two independent variables, while the remaining 46.4% is influenced by other factors outside the research model.These findings imply that organizations should implement fair and transparent reward systems and create a conducive work environment to enhance employee loyalty. This study contributes to human resource management literature by highlighting the importance of rewards and work environment in fostering employee loyalty in the retail sector